The Concise Oxford Companion to English Literature - Edited by Birch, Dinah and Hooper, Katy (Oxford Oxford University Press, 2012)
"Based on the bestselling Oxford Companion to English Literature, this is an indispensable guide to all aspects of English literature. Over 4,900 new and revised A to Z entries give unrivaled coverage of writers, works, historical context, literary theory, allusions, characters, and plot summaries."
Include Appendix
Keywords: English literature -- English-speaking countries